(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The problem of children’s readiness for learning at school is one of the fundamental problems of pedagogy and psychology, has a long prehistory and a relatively short history. The need to prepare children for learning appeared in the process of developing education as a social form of interaction between people of different generations. The article considers the views on the problem of preparing children for schooling in different time periods